Synthesis and DNA-Binding Studies of Two Europium(III) Complexes - Zhang, Ye; Wang, Kai; Zou, Biqun; Liu, Xianxian; Yi, Xianghui (Asian Journal of Chemistry, 2011)
Two new europium(III) complexes EuL3NO3 and EuL2Cl2 (L = coumarin-3-carboxylic anion), have been synthesized and characterized by IR, 1H NMR, 13C NMR, MS and elemental analysis. The DNA binding property of the two complexes has been investigated employing fluorescence spectroscopy. The DNA binding constants for the two complexes have been measured to be 1.64 × 104 L mol-1 and 1.87 × 103 L mol-1 through fluorescence quenching method, indicating that the complexes EuL3NO3 prefer to intercalative binding to DNA. Both of the binding numbers of EuL3NO3 and EuL2Cl2 with DNA have been found to be 1, suggesting that each unit of complex bind with a unit of ct-DNA.